ANALISIS TINGKAT PENGUNGKAPAN DIRI DALAM SECOND ACCOUNT INSTAGRAM DI KALANGAN MAHASISWA ILMU KOMUNIKASI UNIVERSITAS NEGERI JAKARTA - Fahira Novanra; Marisa Puspita Sary; Nada Arina Romli (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
This study aims to find out how self-disclosure is carried out by UNJ communication science students who use a second Instagram account. This study uses qualitative research methods and uses the Johari window theory proposed by Joseph Luth and Harry Ingham. Based on the results of the study, shows that the level of self-disclosure made by second account users is different, this is influenced by the level of closeness of users with their followers in the second account. This study also shows that the user's open areas are daily activities, complaints, and outpourings. While the hidden part of the user is a problem that is too private, such as family problems and friendship conflicts. Meanwhile, for the blind area in the form of responses or comments from content shared by users. The image of the second account user for his followers becomes an unknown part of the user.